Cannabinoids as Therapeutics - Mechoulam, Raphael (Milestones in Drug Therapy, 2005)
In recent years, cannabis research has concentrated on the potential of cannabinoids as therapeutic substances, particularly in serious chronic illnesses such as multiple sclerosis. Most volumes published on cannabinoids so far concentrate on the biological activity, biochemistry and pharmacology, whereas this volume concentrates on the diseases, the physiological effects and therapeutic use of cannabinoids. The volume editor Prof. Mechoulam was the first who isolated the prime active constituent (THC, Tetrahydrocannabiol) of marijuana. He published extensively on the pharmacological activities of cannabinoids. The volume is of interest to researchers and clinicians from pharmacology, neuroscience, and medicinal research.